The Spatial Data Generating Process Matters: Re-Evaluating Socio-Economic and Demographic Drivers of Environmental Justice of Urban Tree Ecosystem Services in Two Mediterranean Cities. - Ruiz-Valero, Ángel; Salvo-Tierra, Ángel Enrique; Peña-Ortiz, Jaime (MDPI, 2026)
To advance the Sustainable Development Goals, it is essential to correct imbalances in how the benefits of urban trees are distributed across different demographic and socioeconomic groups. Environmental justice studies have frequently overlooked assumptions regarding the data-generating process and have not considered spatial confounding. This oversight potentially misestimates patterns of inequity. This study evaluates the sensitivity of inequity to model assumptions using urban tree inventories from Málaga and Sevilla and Bayesian hierarchical models. City-level differences dominated the inequity patterns, and model specification influenced the magnitude, precision, and credibility of estimated effects, though directionality remained consistent. Patterns were highly consistent across the four ecosystem services, indicating that model assumptions affected all services equivalently. Málaga and Seville exhibited divergent inequity patterns, indicating that local urban context mediates these relationships. In Seville, inequity patterns were inconsistent with the luxury hypothesis and occurred primarily across age-based demographic strata, whereas in Málaga they manifested predominantly along ethnicity, with weaker evidence of income inequities. We advocate for explicitly modeling spatial data-generating processes and comparing conventional versus confounding-mitigated approaches. This city-specific rigor is essential for urban planners to prevent resource misallocation, ensuring that tree-planting strategies address genuine inequities rather than methodological biases.
Keywords: Ecología - Aspectos económicos; Ecosistemas - Gestión; Estadística bayesiana; Árboles de ciudad; Bayesian; Ecosystem services; Environmental justice; Green-infrastructure; Urban-forestry; Socio-economic; Spatial-statistics; Urban-trees